Regulation of DELLA Proteins by Post-translational Modifications. (4th September 2020) - Blanco-Tourin, Noel; Serrano-Mislata, Antonio; Alabad, David
Abstract: DELLA proteins are the negative regulators of the gibberellin (GA) signaling pathway. GAs have a pervasive effect on plant physiology, influencing processes that span the entire life cycle of the plant. All the information encoded by GAs, either environmental or developmental in origin, is canalized through DELLAs, which modulate the activity of many transcription factors and transcriptional regulators. GAs unlock the signaling pathway by triggering DELLA polyubiquitination and degradation by the 26S proteasome. Recent reports indicate, however, that there are other pathways that trigger DELLA polyubiquitination and degradation independently of GAs. Moreover, results gathered during recent years indicate that other post-translational modifications (PTMs), namely phosphorylation, SUMOylation and glycosylation, modulate DELLA function. The convergence of several PTMs in DELLA therefore highlights the strict regulation to which these proteins are subject. In this review, we summarize these discoveries and discuss DELLA PTMs from an evolutionary perspective and examine the possibilities these and other post-translational regulations offer to improve DELLA-dependent agronomic traits.